Floristic composition of Shamansir mountain, West Saudi Arabia, as sustainable economic resources - Abeer M. Kutby; Nouf Ali Asiri; Emad A. Alsherif; Mohamed A. Fadl (Scientific Reports)
Abstract Shamansir Mountain is a part of the Sarawat Mountains, western Saudi Arabia. The current study intends to investigate Shamansir Mountain’s plant wealth as well as the impact of direction and height on the mountain’s floristic makeup. The study’s findings, which included 152 species from 124 genera and 46 families, demonstrated how diverse Mount Shamansir’s vegetation is. More than 40% of all species found in the research area belonged to the Asteraceae, Poaceae, Apocynaceae, and Solanaceae families. The obtained results showed that the number of species, genera, and families increases with elevation. These increases from the lowest elevation to the greatest height were, respectively, 280.7%, 286.3%, and 100%. The results showed that the eastern side of the mountain had 36.8%, 27.7%, and 33.3% more species, genera, and families than the western side. Hemicryptophytes made up the smallest percentage of all life forms, at 3%, while therophytes made up the largest, at 44%, followed by chamaephytes at 25%. At 29.6% of all species recorded, the Saharo-Sindian chorotype has the greatest number of monoregional species. Despite Saudi Arabia’s low endemic plant population, one endemic species—Teucrium popovii R.A. King—has been identified. Many of the recorded species are of high economic value. 22 wild crop-related species were discovered in the studied area, while medicinal species comprise 57.8% of the total species in the given list. The study recommends that the Saudi government designate Mount Shamansir as an environmentally protected region, according to the report.